The Effectiveness of Negative Pressure Therapy in Diabetic Foot Ulcers with Elevated Protease Activity: A Case Series - Izzo, Valentina (Adv Wound Care (New Rochelle), 2017)
Objective: Despite several works have described the usefulness of negative pressure therapy (NPT) in the treatment of diabetic foot ulcers (DFUs), no studies have reported its ability in the proteases modulation in DFUs. The aim of this work was to evaluate the role of NPT as a protease-modulating treatment in DFUs. Approach: We conducted a prospective study of a series of diabetic patients affected by chronic DFUs. Each ulcer was assessed for matrix metalloproteinases (MMPs) activity with a protease status diagnostic test at the baseline and after 2 weeks of NPT. Results: Four patients were included. All patients had type 2 diabetes with a disease duration of ≈20 years. A1c was 79.5 ± 15.3 mmol/mol. Ulcer area was >5 cm(2) in all cases. All wounds showed elevated protease activity (EPA) at the baseline. After 2 weeks, all patients showed a normalization of MMPs activity. Innovation: NPT showed its effectiveness in the reduction of EPA in chronic DFUs. Conclusion: This study confirms the role of NPT in the positive modulation of protease activity also in chronic DFUs.